Geometric and topological AI for molecular sciences - Wee, Junjie (Nanyang Technological University, 2023)
Data-driven sciences are widely regarded as the fourth paradigm of sciences that will fundamentally change the society and our daily lives. Indeed, artificial intelligence (AI) models have already revolutionized and transformed various data-intensive industries. Machine learning (ML) and deep learning models have achieved unprecedented extraordinary performance in image, text, audio, video, and network data analysis. This is largely due to the rise in three major advancements, i.e., accumulation of big data, rise in computational power, and design of highly efficient algorithms. In particular, AlphaFold2 made a remarkable achievement for protein-folding problems which heralds a new era for AI-based molecular data analysis for materials, chemistry, and biology.